Diagnosis of the risk, or existence of immunodeficiency state in children associated with sub-atrophy and petrification of the thymus - Yu. I. Rovda; A. V. Vedernikova; A. V. Shabaldin; I. K. Khalivopulo; M. L. Filipenko; N. N. Minyailova; O. V. Shmakova; G. A. Otstavnov; T. M. Vakulova; O. S. Bukhtoyarova; N. V. Krasnova; T. A. Anchikova; et al. (Медицинская иммунология, 2025)
Timely diagnosis of immunodeficiency states (IDS) in children still presents significant issues, especially, when they develop due to failure of the thymus. Thymus pathology may be caused not only by fetogenetic reasons, but also by premature age-related involution caused by the impact of “excessive” stress factors such as infection, continuous hunger, chemotherapy, radiation exposure (including X-ray studies), prolonged hypoxia, tuberculosis infection, tumor growth, etc. Secondary involution processes in the thymus may lead not only to its sub-atrophy (microthymus), but also be accompanied by petrification, leading to irreversible loss of functioninal parenchyma. More often than any mentioned reasons, such deleterious effects are assigned to viral infections, especially in cases of proven thymic infections, with SARS-CoV-2 virus taking a significant place. Clinical manifestations of immune deficiency can persist for several months (or more), from the moment of past pathogenic exposure (usually, infectious factor), over the time required for evolving a petrified structure and its spread. Such pronounced pathomorphosis of the thymus gland is uncommonly diagnosed during the lifetime by means of ultrasound examination. This is, mainly, a pathomorphological finding, when, for example, a life-threatening infection is a manifestation of the already evolved IDS. The immediate cause must be sought via the preceding monitoring. This is a relevant reason for identifying a risk group of such patients performed at the pre-clinical stage of the above-mentioned conditions, with subsequent provision of these patients with both timely diagnostics, conservative drug support (or radical treatment), and a safe epidemiological environment. Our results suggest a significant diagnostic role of ultrasound examination of the thymus for early verification of its critical involution (i.e., sub-atrophy), especially, persisting changes and signs of petrification. Upon revealing these signs in the patient, being combined with high infectious, immune-mediated morbidity and low concentration of TREC copies in nucleated blood cells in a dry drop preparations (less than 500 copies), specific recommendations are offered for the final exclusion of highly probable immunodeficiency disorder.